Evaluation of Gymnastics Sports Development in Pati Regency (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This study aims to evaluate the Antecedent (coaching program, availability of facilities and infrastructure, athletes and trainers resources, funding sources, and support from the government). Furthermore, transactions (implementation of training programs, trainer performance, selection of trainers and athletes acceptance, use of facilities and infrastructure, and coordination. The outcome of the success/achievement of training in gymnastics in Pati Regency. This research is qualitative. The approach used the countenance evaluation model, research data sources, namely administrators, trainers, athletes, athletes' parents, and supporting staff. The results of this study are antecedent which includes an excellent gymnastic training program, because the coaching program can be implemented, facilities and infrastructure are moderate because the facilities used are adequate, but the infrastructure is lacking, support from the government is good because support is available every year, athletes trainers and administrators good because it is competent, funding is moderate because the source of funds is only from the local government. Transactions that include the implementation of a good coaching program, a good coach acceptance system, because the trainer is appointed from a former certified athlete, the athlete's acceptance system is good, because it is based on championship results each year, good coordination between administrators, government, coaches, athletes, and parents. The outcome, the success of a good achievement coaching program is because the achievements are ongoing every year; the welfare of athletes and coaches is moderate because pocket money is still a little.